Chicago Paper - Height of Gas Cap in Safety Lamp (with Discussion) - C. M. Young (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1920)
The safety lamp is the most common and convenient apparatus for detecting inflammable gases in mines, the presence of gas being shown by a blue flame, called the cap, if the wick has been lowered to suppress the luminous flame. The height of the cap increases with the proportion of gas and with the temperature of the lamp flame. Lamps of the Wolf type, the fuel of which is benzine, have a hotter flame than lamps in which vegetable oils are used, such as the Davy, and the Clanny, and are more sensitive than the latter and their many modifications. The Piehler alcohol lamp gives a still higher cap while the Clowes hydrogen lamp is most sensitive of all. While the effect of the temperature of the source of ignition is well known, the writer knows of no previous attempt to correlate the change of this temperature with change of the height of the cap produced, In order to determine the height of the cap at various temperatures, it was necessary to have a source of ignition the temperature of which could be accurately controlled over a considerable range. This condition was met by a coil of wire of high fusing point heated by an electric current controlled by a variable resistance. The use of a coil offered the further advantage of freedom from complications due to the flame of a burning fuel. Such a flame, being itself of variable height, would to some extent raise or lower the elevation of the base of the cap and therefore add to the difficulty of determining the height of the cap. Besides this, the presence of a small cap from the lamp fuel, commonly known as the "fuel cap," would interfere with the observation of small gas caps. After some experiment, a coil was made of platinum wire, No. 26, diameter 0.016 in. The coil was 17/64 in. (6.746 mm.) in outside diameter and had eight full turns in a length of 1/2 in. (12.69 mm.). This was connected to an electric circuit through an adjustable resistance, as shown in Fig. 1. In order to measure the temperature, a thermocouple was inserted in the center of the coil; the leads passed out at the ends and were ccnducted to a millivoltmeter. It is probable that the current of air passing upward through the coil resulted in the indication of a tempera-